Design and development of ICCA as a dual inhibitor of GPIIb/IIIa and P-selectin receptors - Chen H; Lu A; Zhang X; Gui L; Wang YN; Wu J; Feng H; Peng S; Zhao M (Drug Design, Development and Therapy, 2018)
Haiyan Chen,1 An Lu,1 Xiaoyi Zhang,1 Lin Gui,1 Yaonan Wang,1 Jianhui Wu,1 Hua Feng,1 Shiqi Peng,1 Ming Zhao1,2 1Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Beijing Laboratory of Biomedical Materials, College of Pharmaceutical Sciences, Capital Medical University, Beijing, People’s Republic of China; 2Department of Biomedical Science and Environmental Biology, Kaohsiung Medical University, Kaohsiung, Taiwan Background: The impact of upregulation of platelet membrane glycoprotein (GP)IIb/IIIa and P-selectin on the onset of arterial thrombosis, venous thrombosis, and cancer encourages to hypothesize that dual inhibitor of GPIIb/IIIa and P-selectin receptors should simultaneously inhibit arterial thrombosis, block venous thrombosis, and slow tumor growth. Methods: For this reason, the structural characteristics and the CDOCKER interaction energies of 12 carbolines were analyzed. This led to the design of 1-(4-isopropyl-phenyl)-β-carboline-3-carboxylic acid (ICCA) as a promising inhibitor of GPIIb/IIIa and P-selectin receptors. Results: The synthetic route provided ICCA in 48% total yield and 99.6% high-performance liquid chromatography purity. In vivo 5 µmol/kg oral ICCA downregulated GPIIb/IIIa and P-selectin expression thereby inhibited arterial thrombosis, blocked venous thrombosis, and slowed down tumor growth, but did not damage the kidney and the liver. Conclusion: Therefore, ICCA could be a promising candidate capable of downregulating GPIIb/IIIa and P-selectin receptors, inhibiting arterial thrombosis, blocking venous thrombosis, and slowing down tumor growth. Keywords: thrombosis, cancer, GPIIb/IIIa, P-selectin